Assertive training and family psychological education therapy on adolescents self-esteem in prevention of drug use in boarding school - Ramadhan, Indah; Keliat, Budi; Wardani, Ice (International Journal of Advanced Nursing Studies, 2018)
Adolescents are prone to use drugs when they have low self-esteem. Assertiveness training and family psychological education therapies are mental health nursing specialist interventions that are expected to increase adolescent self esteem so that adolescent has ability to prevent drug use. This study aims to determine the effect of assertiveness training and family psychological education therapy on adolescent self-esteem in the prevention of drug use in boarding schools. The research design was a quasi-experimental pre-post test with a control group. Sixty four adolescent students at the boarding school were selected using purposive sampling technique and cluster random sampling. The intervention group 1 only received general nursing intervention and the intervention group 2 received general nursing intervention, assertiveness training, and family psychological education therapy. The results showed that the self-esteem of adolescent students increased significantly after receiving nursing intervention and in the high self-esteem category (p = 0.017), after assertiveness training and family psychological education therapy, adolescent self-esteem in the intervention group 2 increased greater than only general nursing intervention ( P = 0, 000) with the high self-esteem category. There is the influence of assertiveness training and family psychological education therapy on adolescent self-esteem in prevention of drugs uses in a boarding school. Community health center is recommended to do nursing care in school through school health unit program either by primary care nurse or nurse specialist of mental health nursing.